Technical training methodology for qualified table tennis athletes - Dedlovskaya, M.V.; Zolotukhina, I.A.; Tulchansky, D.F. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to theoretically develop and experimentally test the effectiveness of a method for technical training of qualified athletes involved in table tennis at the stage of improving sports skills using a large number of balls. Methods and structure of the study. To solve the set tasks and achieve the set goal, the work used the analysis of scientific and methodological literature, pedagogical testing, pedagogical experiment, mathematical and statistical methods. Results and conclusions. The developed methodology of technical training of athletes using the BKM method in the training process allows to significantly increase the density of technical actions, improve coordination of movements and develop the ability to quickly respond in multitasking conditions.